Microcyle Conidiation in Filamentous Fungi - Jung, Boknam (The Korean Society of Mycology, 2014)
The typical life cycle of filamentous fungi commonly involves asexual sporulation after vegetative growth in response to environmental factors. The production of asexual spores is critical in the life cycle of most filamentous fungi. Normally, conidia are produced from vegetative hyphae (termed mycelia). However, fungal species subjected to stress conditions exhibit an extremely simplified asexual life cycle, in which the conidia that germinate directly generate further conidia, without forming mycelia. This phenomenon has been termed as microcycle conidiation, and to date has been reported in more than 100 fungal species. In this review, first, we present the morphological properties of fungi during microcycle conidiation, and divide microcycle conidiation into four simple categories, even though fungal species exhibit a wide variety of morphological differences during microcycle conidiogenesis. Second, we describe the factors that influence microcycle conidiation in various fungal species, and present recent genetic studies that have identified the genes responsible for this process. Finally, we discuss the biological meaning and application of microcycle conidiation.